KAJIAN MUTU BAJA TULANGAN SIRIP YANG TELAH TERKOROSI SEPULUH TAHUN - Kirman M.; Supriadi . (JURNAL STANDARDISASI, 2007)
Deformed bars steel is used on the structures as reinforcement for increasing strength and safety of structure sand human in surrounding. Construction processes of a concrete structure are usually delayed for several years due to some reasons. Deformed bars steel that are not completed be covered by concrete it will become corroded by natural environment. Effect of corrosion to the quality of bars steel are need to assess base on the qualityrequirement of Indonesia national standard (SNI 07-2052-2002). The Quality requirement items on the standard that are possible affected by corrosion are tensile, bending, and dimension. Furthermore, performance of deformed bars steel after ten years corrosion are need to be evaluated. Assessment results presented that the deformed bars steel are corroded by general corrosion that caused an increasing of surface roughness of bars steel. The increasing of roughness will increase the bond strength. And the corroded deformed bars steel are still comply to the SNI standard with BJTS-40 class.